Tailored Feedback and Worker Green Behavior: Field Evidence from Bus Drivers - Adriaan Soetevent; Gert-Jan Romensen (Tinbergen Institute, 2017)
How to engage workers in conservation efforts when the company pays the bill? In a field experiment with 409 bus drivers, we investigate the potential of targeted peer-comparison feedback and on-the-road coaching. Drivers receive individualized reports with peer-comparison messages on multiple driving dimensions. In addition, coaches quasi randomly provide drivers with in person coaching moments on the bus. Based on 800,000 trip-level observations, we find that the targeted peer-comparison treatments do not improve driving. On-the-road coaching significantly improves driving on multiple dimensions but only temporarily. Further analysis reveals negative interaction effects between the two programs.
Keywords: D2; M5; Q5; 330; peer comparisons; coaching; worker motivation; fuel conservation